Retrospective study of 151 patients with cutaneous leishmaniasis treated with meglumine antimoniate - Armando de Oliveira Schubach; Keyla B. Feldman Marzochi; João Soares Moreira; Tânia Maria Pacheco Schubach; Marcelo Lodi Araújo; Antônio Carlos Francesconi do Vale; Sonia Regina Lambert Passos; Mauro Célio de Almeida Marzochi (Sociedade Brasileira de Medicina Tropical (SBMT), 2005)
We retrospectively analyzed a series of 151 cases of cutaneous leishmaniasis treated between 1967 and 1982. One-hundred-and-thirty-nine (92%) patients presented with active lesions and were treated with daily doses of meglumine antimoniate: 81 adults received a 5-ml vial IM and 58 children received 1 to 5ml. Forty-five (32.4%) patients underwent continuous treatment with meglumine antimoniate for 25 to 116 days without rest intervals, and 94 (67.6%) intermittent treatment with 2 to 5 series of meglumine antimoniate. Intermittent series could include schedules of daily IM applications for 10 to 25 days each and intervals varying from 10 to 60 days. Antimony dose was calculated for 66 (47.5%) patients and ranged from 3.9 to 28.7 Sb5+/kg/day. Of these, 35 patients received >10mg and 31 patients <10mg Sb5+/kg/day. Median time of healing was longer for lesions on the legs and feet - 67.5 days versus 48.7 days (p < 0.001) for other sites. However, there were no significant differences in the median time of healing between adults and children, intermittent and continuous regimens or high and low antimony doses. Fifty-one patients were reassessed 5 to 14 years after treatment and showed no evidence of disease. These results support further investigation (clinical trials) on treatment using low doses of antimony.